Mikhail Bakhtin : the Duvakin interviews, 1973 - Gratchev, Slav N.; Marinova, Margarita (Margarita D.); Marinova, Margarita (Margarita D.) (Bucknell University Press, 2019)
"Mikhail Bakhtin has exercised an enormous influence on Western scholars through his theoretical studies of literature, but he has not left behind any personal accounts. The present translation is the first to provide insight into his views of life under Stalin and beyond. The 12-hour-long, six interviews conducted by Duvakin with Bakhtin in 1973 reveal to us his memories of the formative moments in his educational background; how he reacted to the February and October Revolutions; his impressions of many leading political and intellectual figures during the first two decades of the twentieth century; what he thought of poetic language in general, and famous Russian and Soviet poets in particular, etc. The interviews invite a more intimate look into Bakhtin's understanding of the value and powers of Art, and encourage the reader to enter the conversation alongside the two voices speaking to us from a distant, yet eerily relevant century"--